Breaking Silence: The Power of Peer Support in Alleviating Student Loneliness - Veronica Lowinsky; Maria Nugraheni Mardi Rahayu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
University life is a transitional period that is vulnerable to loneliness due to changes in social environment, academic pressure, and demands for independence. This study aimed to examine the relationship between peer social support and the level of loneliness among students at Satya Wacana Christian University (UKSW). This research employed a quantitative approach with a correlational design. The sample consisted of 100 active students from UKSW, selected using accidental sampling. The instruments used were the Social Provisions Scale (SPS) to measure peer social support and the UCLA Loneliness Scale Version 3 to assess loneliness levels. Data analysis was conducted using Pearson correlation and partial correlation across dimensions. The results showed a significant negative relationship between peer social support and loneliness. The higher the perceived social support, the lower the level of loneliness experienced by the students. All aspects of social support, such as attachment, guidance, and reassurance of worth, were found to have significant correlations with various dimensions of loneliness. The implication of this study highlights the importance for higher education institutions to facilitate the strengthening of peer relationships through mentoring programs, social engagement activities, and the development of interpersonal skills to prevent social isolation and support students’ psychological well-being.Masa perkuliahan merupakan periode transisi yang rentan terhadap perasaan kesepian akibat perubahan lingkungan sosial, tekanan akademik, dan tuntutan kemandirian. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial teman sebaya dengan tingkat kesepian pada mahasiswa Universitas Kristen Satya Wacana (UKSW). Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 100 mahasiswa aktif UKSW yang diambil menggunakan teknik accidental sampling. Instrumen yang digunakan yaitu Social Provisions Scale (SPS) untuk mengukur dukungan sosial teman sebaya dan UCLA Loneliness Scale Version 3 untuk mengukur tingkat kesepian. Analisis data dilakukan menggunakan korelasi Pearson dan korelasi parsial antar aspek. Hasil penelitian menunjukkan terdapat hubungan negatif yang signifikan antara dukungan sosial teman sebaya dengan kesepian pada mahasiswa. Semakin tinggi dukungan sosial yang dirasakan, maka semakin rendah tingkat kesepian yang dialami. Seluruh aspek dukungan sosial seperti attachment, guidance, dan reassurance of worth memiliki hubungan yang signifikan terhadap berbagai dimensi kesepian. Implikasi dari penelitian ini adalah pentingnya lembaga pendidikan tinggi untuk memfasilitasi penguatan relasi sosial antar mahasiswa melalui program mentoring, kegiatan sosial, dan pengembangan kapasitas interpersonal guna mencegah isolasi sosial dan mendukung kesejahteraan psikologis mahasiswa.